Pengaruh Kelengkapan Produk, Harga Dan Merek Terhadap Keputusan Pembelian Produk H&M (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Faruq, Muhammad; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims examine and explain the impact of product completeness, price and brand on purchasing decisions of h&m produkct. This quantitative research employ the maholtra formula, tested using multiple steps in spss. The results indicate that product complenteness, price and brand have partial and simultaneous effects on purchasing decisions. Keywords: Product Completeness, Price Brand, Purchasing Decision.